PENERAPAN METODE EJA : PENINGKATAN KETERAMPILAN MEMBACA DAN MENULIS PADA SISWA KELAS 1 MIS PSM BANJARSARI - Fatayati, Vita Sun; T.G Samosir, Hendro (eL-Muhbib jurnal pemikiran dan penelitian pendidikan dasar, 2024)
The aim of this research is to find out how the spelling approach has improved the reading and writing abilities of first grade students at MIS PSM Banjarsari. The researcher participated directly in this activity as part of the qualitative research methodology used in this research. Because he taught homeroom, the researcher was actively involved in this research. To determine students' interests and talents, initial reading comprehension tests are used along with student behavior or habit observation sheets. This allows the methods used to be applied in an acceptable manner. In addition, the six students received additional hours of guidance from the researchers. Data are presented using line graphs in analyzes based on analysis within and between conditions. Spelling methods are effective for beginning readers, data shows. This is shown by the increase in the percentage of students in class 1 who have initial reading skills.